Sonication to improve the yield in culture-negative peri-prosthetic joint infection. Issue 1 (2nd January 2019) - Abou El-Khier, Noha Tharwat; El-Kazzaz, Samah Sabry; Elgeidi, Adham; Elganainy, Abd El Rhman
ABSTRACT: Peri-prosthetic joint infection (PJI) is a catastrophic complication, after joint arthroplasty. Culture-negative PJI presented 7–39% of PJI cases at most health-care centers. We aimed to investigate the diagnostic accuracy of sonication fluid culture (SFC) with the respective peri-prosthetic tissue cultures (PTC). Also, to evaluate the efficacy of sonication in PTC-negative PJI. Peri-prosthetic tissue specimens were subjected to microbiological culture and histo-pathological examination. Retrieved prosthesis components were sonicated. SFC was examined. One hundred and seventy patients had PJI and 95 were aseptic failures. SFC was positive in 120 patients (70.5%). For PTC, 80 of 170 samples (47.1%) were positive; all reveal the same bacterial species with the corresponding SFC. In 50 patients, both PTC and SFC cultures of the prosthesis were negative. There were 40 negative PTC samples proved to be positive by SFC, 39 displayed Staphylococcus epidermidis, and only one sample yielded Propionibacterium acne. Biofilm formation was detected in 22 (56.4%) out of the 39 S. epidermidis isolates. The overall sensitivity of SFC compared to PTC was (70.6% versus 47.1%). SFC represents a sensitive, accurate, easy diagnostic strategy representing increased sensitivity contrasted with PTC. S. epidermidis, although an important commensal, is considered the most significant pathogen in the context of PJI.